Biosorption and bioaccumulation of gold by a strain of Lysinibacillus sp. insolated of an alluvial mine (2017)
Severe environmental and social problems rise up due to the struggle between power and mining activity. Gold mining is an increasing economic activity in Colombia however, it is also the cause of serious environmental and violence problems in the country. A strain of Lysinibacillus sp., was isolated from an area of an active alluvial gold mining exploitation at El Bagre, Antioquia. It was evident the biosorption and bioaccumulation capacity of the strain in both living and dead cells. For death biomass the percentage of recovery of gold were 86% and 83% for 60æg/mL and 20æg/mL respectively in nutrient broth; while in minimum salt medium were 40% and 21% for the same concentrations. Similarly, in bioassays with live biomass the percentages of gold concentrations were 79% and 2% for nutrient broth; whereas in minimum salt medium were 25% and 46%. According to this, dead cells show a higher percentage of gold recovery through time in comparison to living cells and the development of them is better in higher concentrations of gold and in nutrient broth. Additionally, the presence of S-layer confirms the capacity of this protein to adsorb metals, in this case gold. This can be a potential alternative for processes in biomining related with the extraction of gold in an environmental sustainable approach.